Blinding assessment in randomised sham-controlled trials of acupuncture:protocol for a systematic survey - Ling Li; Xin Sun; Jiali Liu; Minghong Yao; Yong Fu; Jiahui Yang; Xiaochao Luo (BMJ Open)
Introduction Although various sham acupuncture techniques have been employed to ensure blinding in randomised controlled trials (RCTs) of acupuncture, the effectiveness of blinding in these trials and its influence on trial effect size estimates remain unclear. The objectives of this study are the following: (1) to investigate the proportion and study characteristics of sham-controlled trials reporting on blinding assessment, (2) to assess the blinding effectiveness of different types of sham acupuncture, (3) to investigate the relationship between blinding effectiveness and effect sizes in acupuncture RCTs.Methods and analysis We will search PubMed and EMBASE from inception to 1 January 2025 to identify RCTs that compared acupuncture with sham acupuncture in humans with any disease or symptom, with no restrictions on language. Paired investigators will independently determine eligibility and use pilot-tested standardised forms for data extraction. We will calculate the proportion of sham-controlled trials that assessed and reported blinding success and conduct descriptive analyses of general study characteristics, acupuncture treatment details, sham acupuncture details and blinding assessments for included trials. We will assess the effectiveness of blinding success using the James blinding index (BI) and Bang BI, and pool data from included trials using random-effects models. We will use Hedges’ g, a standardised mean difference, with its 95% CI, to calculate treatment effects. We will use Pearson’s r correlation coefficient to assess the relationship between blinding effectiveness and trial effect sizes when variable distributions meet the assumptions of normality and linearity; otherwise, we will consider employing non-parametric tests. When sufficient data are available, we will also use random-effects meta-regression to explore the relationship.Ethics and dissemination Ethical approval is not required. The findings of this study will be disseminated through peer-reviewed publications, conference presentations and condensed summaries for clinicians, health policymakers and guideline developers regarding the design, conduct, analysis and interpretation of blinded assessment of sham acupuncture RCTs.Study registration Open Science Framework (https://doi.org/10.17605/OSF.IO/B3U7K).